The Role of Competitive Advantage in Mediating the Influence of Business Strategy and Traditional Work Ethic on Entrepreneurial Performance at Warung Madura Grocery Store in Surabaya - Dedy Ahmadi; Nurul Hidayat; Ainorrofiqie; Fuji Santoso; Moh Naufal Abror (Majapahit Journal of Islamic Finance and Management, 2026)
Study This is studies causal with approach quantitative purposeful​ for test influence strategy business and ethos Work traditional to performance entrepreneurship, as well as role superiority compete as variables mediation in the store grocery store Madura stalls in Surabaya City. Population in study This covers 980 stores grocery store Madura stalls are spread across 14 sub-districts in Surabaya, with amount sample A total of 250 respondents were selected use purposive sampling technique. Research results show that strategy business and ethos Work traditional influential significant to performance entrepreneurship, good in a way direct and no direct through superiority compete. Strategy effective business, such as differentiation product, efficiency costs, and market focus, as well as values ethos Work traditional like honesty, perseverance, and responsibility answer, proven support achievement superiority compete. Advantages compete play a role as a mediator that strengthens influence second variables to performance entrepreneurship. Findings This confirm importance strengthening strategy business and values ethos Work traditional in increase Power competitiveness and performance business shop grocery store Madurese food stall in Surabaya.